Special issue “magma migration and eruptions in a volcanic group: case studies for the 2017–2018 activity of the Kirishima Volcano Group and other global examples” - Takayuki Kaneko; Mie Ichihara; Kostas I. Konstantinou; Antonio Costa; Yasuo Miyabuchi; Koki Aizawa (Earth, Planets and Space)
Graphical Abstract